Bilingualism: A Global Public Health Strategy for Healthy Cognitive Aging - Mendis, Sahan Benedict; Raymont, Vanessa; Tabet, Naji (Frontiers in Neurology, 2021)
Dementia is a global public health priority which costed global societies $818 billion in 2015 and is disproportionately impacting low and middle-income countries (LMICs). With limited availability of disease modifying drugs to treat Alzheimer’s disease (AD), researchers have increasingly focused on preventative strategies which may promote healthy cognitive ageing and mitigate the risk of cognitive impairment in ageing. Lifelong bilingualism has been presented as a both a highly debated and promising cognitive reserve factor which has been associated with better cognitive outcomes in ageing. A recent metanalysis has suggested that bilingual individuals present on average 4.05 years later with the clinical features of AD than monolinguals and bilinguals are diagnosed with AD approximately 2.0 years later than monolingual counterparts. In this perspective piece we critically evaluate the findings of this metanalysis and consider the specific implications of these findings to LMICs. Furthermore, we appraise the major epidemiological studies conducted globally on bilingualism and the onset of dementia. We consider how both impactful and robust studies of bilingualism and cognition in older age may be conducted in LMICs. Given the limited expenditure and resources available in LMICS and limited successes of clinical trials of disease modifying drugs we propose that bilingualism should be positioned as important and specific public health strategy for maintaining healthy cognitive ageing in LMICs. Finally, we reflect upon the scope of implementing bilingualism within the education systems of LMICS and the promotion of bilingualism as a healthy cognitive ageing initiative within government policy.